Hayman’s diallel analysis for yield-related traits in F1 and F2 durum wheat (Triticum durum Desf.) progenies - Insaf Bentouati; Abderrahmane Hannachi; Zine El Abidine Fellahi; Abdelhamid Mekhlouf; Aleksandra O. Utkina; Mohamed S. Shokr; Nazih Y. Rebouh (PLoS ONE, 2026)
This study employed Hayman’s diallel analysis to investigate the inheritance patterns of eight agronomic traits in durum wheat ( Triticum durum Desf.) using a 4 × 4 half-diallel mating design evaluated across F 1 and F 2 generations. Field trials were conducted at the INRAA experimental station in Sétif, Algeria, during the 2021–2022 and 2023–2024 growing seasons. The analysis revealed significant genotypic variation across all studied traits, with distinct inheritance patterns emerging between generations. Plant height was predominantly governed by additive gene action. In contrast, spike length and number of grains per spike shifted from overdominance in F 1 to partial dominance in F 2 , reflecting enhanced additive effects post-recombination. Yield components, including spike weight, number of spikes per plant, and grain yield, exhibited persistent non-additive inheritance and overdominance across generations, indicating limited early-generation selection efficiency. Dominance effects were significant in F 1 but diminished in F 2 for most traits, suggesting a recombination-mediated breakdown of heterotic patterns. Allele distribution was asymmetric, highlighting unequal parental contributions and the potential for heterosis exploitation. Most traits were controlled by a single gene or a closely linked gene block, as indicated by the h ^ 2 / H ^ 2 ratio. High broad-sense heritability, in contrast to variable narrow-sense heritability, suggests the need for generation-specific breeding strategies. These findings support pedigree selection for additive traits in early generations and recurrent or advanced-generation selection for yield components, thereby optimizing durum wheat improvement under semi-arid Mediterranean conditions.